2022
DOI: 10.1186/s12872-022-02527-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between epicardial fat volume on cardiac CT and atherosclerosis severity in three-vessel coronary artery disease: a single-center cross-sectional study

Abstract: Background The ideal treatment strategy for stable three-vessel coronary artery disease (CAD) patients are difficult to determine and for patients undergoing conservative treatment, imaging evidence of coronary atherosclerotic severity progression remains limited. Epicardial fat volume (EFV) on coronary CT angiography (CCTA) has been considered to be associated with coronary atherosclerosis. Therefore, this study aims to evaluate the relationship between EFV level and coronary atherosclerosis s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Several studies have found that EAT was correlated with the occurrence and severity of coronary artery disease [ 23 , 24 ]. It remains controversial, however, whether CSF could be considered as the primary stage of coronary artery disease [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that EAT was correlated with the occurrence and severity of coronary artery disease [ 23 , 24 ]. It remains controversial, however, whether CSF could be considered as the primary stage of coronary artery disease [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%